Efficacy of salvage chemotherapy in diffuse large B cell lymphoma with primary treatment failure according to putative cell of origin. Issue 4 (21st March 2019) - Badar, Talha; Hamadani, Mehdi; Bachanova, Veronika; Maddocks, Kami J.; Umyarova, Elvira; Chavez, Julio C.; Epperla, Narendranath; Chhabra, Saurabh; Xavier, Ana C.; Karmali, Reem; Salhab, Mohammed; Reddy, Nishitha; et al.
Abstract: We evaluated outcome of 235 primary treatment failure (PTF) diffuse large B-cell lymphoma (DLBCL) patients based on salvage chemotherapy regimen and putative cell-of-origin (COO). Patients were divided into two groups; group A ( n  = 38) received high-dose cytarabine containing regimen, either DHAP or ESHAP. Patients in group B ( n  = 197) received ifosfamide, carboplatin, and etoposide (ICE) +/− rituximab. No difference in overall response rates (CR + PR) was observed based on salvage chemotherapy regimen and COO. After adjustment for the presence of ultra high-risk features, overall survival of germinal center B-cell like (GCB) DLBCL patients in group A was not significantly different from survival in group B (HR 0.86, 95% CI 0.46–1.60, p  = .64). Similarly, within non-GCB DLBCL cohort, survival in group A was comparable to group B (HR 0.53, 95% CI 0.20–1.44, p  = .21). We did not find an outcome difference between two commonly used salvage chemotherapy regimens in patients with PTF DLBCL based on COO.